2010
DOI: 10.1007/s00424-010-0862-9
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and beta-cell dysfunction

Abstract: Diabetes mellitus type 1 and 2 (T1DM and T2DM) are complex multifactorial diseases. Loss of beta-cell function caused by reduced secretory capacity and enhanced apoptosis is a key event in the pathogenesis of both diabetes types. Oxidative stress induced by reactive oxygen and nitrogen species is critically involved in the impairment of beta-cell function during the development of diabetes. Because of their low antioxidant capacity, beta-cells are extremely sensitive towards oxidative stress. In beta-cells, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
214
1
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 265 publications
(231 citation statements)
references
References 206 publications
8
214
1
2
Order By: Relevance
“…In patients with type 2 diabetes, there is, over time, a progressive loss of beta cells due to increased apoptosis [39][40][41][42]. This increase in cell death is thought to be a consequence, at least in part, of glucolipotoxicity and associated oxidative stress [20,21,43,44]. There is, nonetheless, much that remains unknown regarding the mechanisms of beta cell loss as diabetes progresses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with type 2 diabetes, there is, over time, a progressive loss of beta cells due to increased apoptosis [39][40][41][42]. This increase in cell death is thought to be a consequence, at least in part, of glucolipotoxicity and associated oxidative stress [20,21,43,44]. There is, nonetheless, much that remains unknown regarding the mechanisms of beta cell loss as diabetes progresses.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with type 2 diabetes lose a significant portion of their beta cell mass over time [18,19], and this is believed to be at least in part a consequence of oxidative stress [20,21]. Various lines of indirect evidence suggest that pharmacological interventions that augment glucokinase activity may favour mechanisms that slow or prevent beta cell loss [22,23] or promote beta cell proliferation in vivo [3,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…For pheochromocytoma cells, it has been shown that short-term application of 3-NPA induces a concentration-dependent elevation of ROS [32], whereas others did not detect any effect in the same cell line [33]. As oxidative stress plays an important role in beta cell failure during development and progression of type 2 diabetes [34], we monitored ROS accumulation. Our data demonstrate that 3-NPA had no acute effect on intracellular ROS and even reduced ROS concentration after an exposure time of 1 h (Fig.…”
Section: Mitochondrial Function and [Camentioning
confidence: 99%
“…With persistent hyperglycemia, disproportionate amounts of glucose are delivered to the cells. This results in enhanced glucose flux through glycolysis and the tricarboxylic acid (TCA) cycle (Drews et al, 2010). This leads to an overdrive of the mitochondrial electron transport chain, which generates greater amounts of O 2 •− more than mitochondrial SOD can dismutase , Brand, 2010.…”
Section: Hyperglycemiamentioning
confidence: 99%